1988
DOI: 10.1002/j.1537-2197.1988.tb11263.x
|View full text |Cite
|
Sign up to set email alerts
|

Andromonoecy and Variation in Phenotypic Gender of Passiflora Incarnata (Passifloraceae)

Abstract: We studied the perennial vine Passiflora incarnata Linnaeus (Passifloraceae) in Alachua County, Florida, from May to August 1983 to determine the breeding system and investigate seasonal changes in phenotypic gender of individual plants. Passiflora incarnata is an obligate outcrosser, incapable of self‐fertilization. The major pollinators were carpenter bees (Xylocopa sp.). The proportion of flowers setting fruit was not limited by pollinator service, but the weight of individual fruits and number of seeds/fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
3
2

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 28 publications
0
42
3
2
Order By: Relevance
“…The flowers of the genus Passiflora are highly specialized, with stamens, ovary, and tripartite style elevated onto an androgynophore (see May and Spears, 1988, for illustration). When the flower opens, usually between 1 1 15 and 1200 EST at our study site, the style is located well above the ring of five stamens, stigmas uppermost.…”
Section: Materials and Methods-study Species-mentioning
confidence: 99%
See 1 more Smart Citation
“…The flowers of the genus Passiflora are highly specialized, with stamens, ovary, and tripartite style elevated onto an androgynophore (see May and Spears, 1988, for illustration). When the flower opens, usually between 1 1 15 and 1200 EST at our study site, the style is located well above the ring of five stamens, stigmas uppermost.…”
Section: Materials and Methods-study Species-mentioning
confidence: 99%
“…Maturing fruits significantly influenced gender expression of subsequent flowers on the same branch by decreasing the relative number of hermaphroditic flowers produced and increasing the relative number of male flowers produced. By removing maturing fruits, we were able to increase relative hermaphroditic flower production (May and Spears, 1988). Sexual expression in Passiflora appears to be labile and responsive to resource changes in the immediate floral environment.…”
mentioning
confidence: 98%
“…These results indicate that S. arctopoides does not actively change phenotypic gender expression in response to unsuccessful seed-set on early flowers, unlike other andromonoecious Apiaceae (Hendrix and Trapp 1981;Hendrix 1984) and other taxa Webb 1983, Stanton et al 1987;May and Spears 1988;Diggle 1993). However, herbivory of strictly vegetative tissue prior to flowering could still possibly cause changes in plant size or resource availability that would, in turn, induce gender changes.…”
Section: Discussionmentioning
confidence: 52%
“…Several studies of andromonoecious dicots have demonstrated that destruction of ovaries in hermaphroditic flowers leads to increased hermaphroditic flower production later in the same reproductive season (Hendrix and Trapp 1981;Hendrix 1984;May and Spears 1988). In one case at least (Hendrix and Trapp 1981), flowers at normally staminate positions developed as functional hermaphrodites.…”
Section: Introductionmentioning
confidence: 98%
“…Acer grandidentatum growing in semiarid shrublands also showed reduced femaleness under dry conditions (Barker et al 1982). No effect of water availability was seen in monoecious Ambrosia artemisiifolia L. (McKone and Tonkyn 1986) and in andromonoecious Passiflora incarnata L. (May and Spears 1988). The former authors interpreted the lack of effect of water on sex expression in the Ambrosia species as a reflection of this plant's adaptation to environments in which soil moisture fluctuates widely.…”
Section: Fig 2 Mean Numbers Of Flowers Per Plant (A) and Mean Propomentioning
confidence: 80%